Divenire anziani in diaspora: profili migratori e prospettive di invecchiamento in un confronto tra Italia e Tunisia - Getting Old into Diaspora: migration profiles and prospects for aging in a comparison between Italy and Tunisia - Gloria Frisone (EtnoAntropologia, 2025)
This paper presents the initial results of an ethnographic investigation aimed at analyzing the phenomenon of ‘transnational’ or ‘diasporic’ aging through the migration trajectories of elderly members of the Tunisian diaspora in Italy and, conversely, the Italian diaspora in Tunisia. The research collects life histories, highlighting a complex landscape of experiences, and seeks to position different categories of diasporic aging along a continuum between social disadvantage and privilege. Finally, the intersectional analysis examines the influences of class, gender, and social capital.